2016
DOI: 10.1515/nuka-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Soil heat flux and air temperature as factors of radon (Rn-222) concentration in the near-ground air layer

Abstract: IntroductionRadon (Rn-222), a radioactive gas with a half--life of 3.82 days, is emitted naturally (0.72-1.2 atoms·cm −2 ·s −1 ) from ice-free, unsaturated terrestrial surfaces [1,2]. The Rn-222 concentration in the near-surface air layer is undoubtedly strongly infl uenced by local conditions, which are connected with the environment of the gas emissions to the atmosphere (inter alia: geological formation, soil characteristics -radium content, permeability and porosity, temperature vertical profi le, soil hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The observed diurnal variation of 222 Rn content of the air is similar to that found in southern Finland, 16 Poland, 17 Germany, 23 Czech Republic 24 and China. 25 High values are encountered around the Sun rise when the vertical temperature inversion stratifies the lowermost troposphere.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The observed diurnal variation of 222 Rn content of the air is similar to that found in southern Finland, 16 Poland, 17 Germany, 23 Czech Republic 24 and China. 25 High values are encountered around the Sun rise when the vertical temperature inversion stratifies the lowermost troposphere.…”
Section: Resultssupporting
confidence: 78%
“…16 In Poland the arithmetic mean outdoor 222 Rn activity concentration was 5 Bq m −3 in Łódź, 6 Bq m −3 in Ciosny and 10 Bq m −3 in Kraków. 17 In Slovenia a geometric mean value of 12 Bq m −3 was measured. 18 In New York City, USA, an average outdoor 222 Rn content of 4.2 Bq m −3 in the air was observed during a period of seven years.…”
Section: Instrumentationmentioning
confidence: 99%
“…Several researchers have measured the daily concentration variations of 222 Rn and its short-lived progenies in atmospheric air, but not limited. [9][10][11][12][13][14][15] They have found that the daily concentration variation exhibits correlation with the relative air humidity, and anti-correlation with the air temperature, which indicates that the concentration is mainly influenced by the turbulent diffusion caused by the changes in temperature. However, most of the observed concentrations show a maximum occurring in the early morning and a minimum in the late afternoon.…”
Section: Radionuclidementioning
confidence: 99%
“…Moreover, 222 Rn has long-lived decay products 210 Pb (22.3 y) and 210 Po (138.4 d) possessing long elimination periods in the human body. Being a heavy inert gas, radon is concentrated mostly in soil, near-ground air and lower fl oors of buildings [2,3].…”
Section: Introductionmentioning
confidence: 99%